2010
DOI: 10.1128/jvi.00337-10
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of ICP34.5 Herpes Simplex Virus 1 Replication in Mouse Brain Cells In Vivo

Abstract: Replication-competent forms of herpes simplex virus 1 (HSV-1) defective in the viral neurovirulence factor infected cell protein 34.5 (ICP34.5) are under investigation for use in the therapeutic treatment of cancer. In mouse models, intratumoral injection of ICP34.5-defective oncolytic HSVs (oHSVs) has resulted in the infection and lysis of tumor cells, an associated decrease in tumor size, and increased survival times. The ability of these oHSVs to infect and lyse cells is frequently characterized as exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…The speed with which the virus undergoes cell-to-cell spread was the focus of studies by Markovitz et al 1, 2. They showed that Δγ 1 34.5 virus is capable of viral replication including synaptic spread but that this is slow and inefficient and that by D6–D8 post-infection, intrinsic and immune-mediated anti-viral responses limit Δγ 1 34.5 replication and clear the infection 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The speed with which the virus undergoes cell-to-cell spread was the focus of studies by Markovitz et al 1, 2. They showed that Δγ 1 34.5 virus is capable of viral replication including synaptic spread but that this is slow and inefficient and that by D6–D8 post-infection, intrinsic and immune-mediated anti-viral responses limit Δγ 1 34.5 replication and clear the infection 1 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the construction of a chimeric HSV-1, C134, which is a neurovirulent and is deleted for the γ 1 34.5 gene but expresses the human cytomegalovirus (HCMV) IRS1 gene. The IRS1 gene improves Δγ 1 34.5 replication within tumors and improves its anti-tumor activity in murine tumor models, yet C134 remains as safe as its parent Δγ 1 34.5 virus in lethal dose 50% (LD 50 ) and virus recovery studies 1, 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, deletion of the HSV-1 gamma 34.5 gene limited replication in tumor cells, although recent studies have shown some degree of neurotoxicity in normal brain cells [140]. Another oncolytic virus, the FusOn-H2 virus, was generated by introducing mutations in the PK domain of the viral ICP10 gene, in this virus replication was dependent on the activation of the Ras signaling pathway [93].…”
Section: Engineering More Effective and Selective Vectors Targeting Pmentioning
confidence: 99%
“…[1][2][3] The removal of virulence genes enhances the safety of HSV-1 vectors against serious complications and/or reversion to wild type. [4][5][6] Some of these oncolytic HSV-1 viruses have been approved for clinical trials in breast cancer, 3,7 head and neck carcinoma, 8 glioma, 9 melanoma, 10 non-small-cell lung carcinoma 11 and metastases from colorectal cancer 12 (reviewed in Manservigi et al 13 ). These clinical trials demonstrate that HSV-1 vectors are generally well tolerated at high doses with few side effects.…”
Section: Introductionmentioning
confidence: 99%